Bioelectrical, anthropometric, and hematological analysis to assess body fluids and muscle changes in elite cyclists during the Giro d'Italia - Cebrián-Ponce, Á.; Irurtia, A.; Castizo-Olier, J.; Garnacho-Castaño, M. V.; Espasa-Labrador, J.; Noriega, Z.; Carrasco-Marginet, M. (Biology, 2023)
Simple Summary Giro d`Italia is one of the most demanding races in cycling tour, in which, during the 3 weeks of competition, several physiological adaptations occur. This study aimed to analyze these changes with different methods (bioelectrical, anthropometrical, and hematological analysis) in order to see how body fluids vary in the whole body as the competition progresses, and also in three specific muscle groups (quadriceps, hamstrings, and calves). There were three checkpoint assessments: at the beginning, middle, and end of the race. Results indicated that bioelectrical impedance vector analysis is sensitive to the body fluid changes. A proper homeostatic adaptation was detected during the first half of competition, but the long-term, high intensity exercise would result in profound fluid loss and distribution in the soft tissues. Furthermore, most of these changes happened in the extracellular water compartment, indicating that the state of the cell membranes was maintained in good condition. The calves are the muscle group most sensitive to this analysis. In conclusion, bioelectrical impedance vector analysis is a reliable, non-invasive, and practical method to assess physiological adaptations in athletes.